Strategies To Accelerate The Reduction Of Stunting Prevalence Through Mapping The Physical, Biological And Socio-Cultural Environment At Risk With The Trias Epidemiology Approach - Maulana, Jaya; Fitriyani, Nur Lulu; Nugroho, Santoso Tri; Pangestu, M. Luhur (Journal of Public Health Indonesian, 2025)
Stunting is a serious problem that must be addressed because it has an impact on the quality of human resources that will be dated. The prevalence of stunting cases in Indonesia in 2022 has decreased compared to 2021, which was 21.6%. However, this figure is still above the government's expectations which determine a decrease of up to 14% in 2024. This determination requires comprehensive handling from various parties in reducing the incidence of stunting and preparing a better next generation. This study aims to determine environmental factors that are risk factors for stunting in Pekalongan City through the trias epidemiological approach. This study is a mixed methods study  using an explanatory sequential design with a case control approach. The independent variables to be studied include host and environment variables. The data obtained will be analyzed bivariate and multivalent with data reduction and drawing conclusions from qualitative data. Furthermore, the results of the mix methods analysis  will be included in the SWOT analysis to formulate a strategy to accelerate the reduction of stunting prevalence in Pekalongan City.